KOMPETENSI GURU, GAYA BELAJAR DAN PRESTASI BELAJAR PKN SISWA (Studi Deskriptif Pada Kelas VIII Di SMP Negeri 33 Kabupaten Kaur) - Sahjohan Sahjohan; Riyanto Riyanto (DIADIK, 2021)
This study aims to 1) know the competence of grade VIII teachers of SMP Negeri 33 in Kaur Regency. 2) know the PKN learning styles of students of class VIII of SMP Negeri 33 in Kaur Regency 3) know the learning achievements of students of class VIII of SMP Negeri 33 in Kaur Regency. This research method is descriptive qualitative about teacher competence, learning style with class VII student learning achievement at SMPN 33 Kaur Regency Bengkulu Province. The subjects of this study were VIII grade VIII 33 State Junior High School 33 teachers in Kaur Regency, while the respondents were 30 grade VIII SMP 33 students in Kaur District. Data collection techniques in this study used a questionnaire and observation. The results showed that the ability of Civics Teachers in Class VIII at SMP Negeri 33 in Kaur District in mastering teaching methods and class management needed to be improved to achieve higher professional competence. The learning styles of VIII grade students of SMP Negeri 33 in Kaur Regency are dominantly owned by students of grade VIII at SMP Negeri 33 is the listening learning style, while the learning achievement of PNK students in class VIII at SMP Negeri 33 in Kaur Regency. Enough in the category